Constructed and Floating Wetlands for Sustainable Water Reclamation - Arslan, Muhammad; Afzal, Muhammad; Anjum, Naser A. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Constructed wetlands (CWs) are engineered phytoremediation ecotechnologies. Herein, the two main biotic components, namely, plants and the bacterial community, work synergistically to remove a wide range of pollutants from wastewater. CWs have been used as sole treatment systems or as integrated modules within other types of wastewater-treatment plants (WWTPs), e.g., as tertiary treatment units. This Special Issue and Book gathers and appraises recent research outcomes regarding natural wetlands (i.e., mangroves) and engineered wetlands (constructed/floating systems), and highlights the underlying pollutant-degradation pathways and mechanisms for a wide range of organic and inorganic contaminants.